2021
DOI: 10.3390/nu13020694
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Properties of Human Milk: A Multitude of Defence Tools from Mother Nature

Abstract: The anti-infective properties of breast milk have been known for decades. In recent years, an increasing number of papers have described the variety of bioactive compounds that are present in breast milk with varying degrees of antiviral activity. However, to date, the totality of the properties of these compounds is not fully understood and, above all, their synergistic interaction is not yet known. The purpose of this review is to describe the current knowledge about the antiviral compounds in breast milk, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 51 publications
0
35
0
1
Order By: Relevance
“…Lactoferrin is an iron chelating milk bioactive peptide. Due to its beneficial effects on the development of the gut as well as disease prevention and therapy through anti-inflammatory and anti-viral effects, lactoferrin has been suggested as a therapy for COVID-19 [90,91]. An in vitro study in Caco-2 cells showed that lactoferrin inhibited SARS-CoV-2 replication through promoting anti-viral gene expression and reducing the expression of genes necessary for viral replication including RNA-dependent RNA polymerase (RdRp) and E gene (CoVE) [92].…”
Section: Lactoferrinmentioning
confidence: 99%
“…Lactoferrin is an iron chelating milk bioactive peptide. Due to its beneficial effects on the development of the gut as well as disease prevention and therapy through anti-inflammatory and anti-viral effects, lactoferrin has been suggested as a therapy for COVID-19 [90,91]. An in vitro study in Caco-2 cells showed that lactoferrin inhibited SARS-CoV-2 replication through promoting anti-viral gene expression and reducing the expression of genes necessary for viral replication including RNA-dependent RNA polymerase (RdRp) and E gene (CoVE) [92].…”
Section: Lactoferrinmentioning
confidence: 99%
“…Their concentration decreases in the first 12 weeks after birth, in accordance with an increase in the newborn's own production [14,15]. In addition to providing a passive immunity, breast milk IgAs bind to gut bacteria, hindering their overgrowth, inhibiting pathogens' attachment to the gastrointestinal mucosal surface and neutralizing microbial toxins, thus conferring an antimicrobial defense to the neonatal gastrointestinal tract [16].…”
Section: Immune Healthmentioning
confidence: 99%
“…In particular, IgA levels have been reported to be lower in the mature milk of mothers with gestational diabetes, post-partum stress, anxiety and depression [14]. Furthermore, high levels of IgA, cytokines, oligosaccharides and other immune factors in human milk are associated with a lower risk of food allergy during childhood [15,16]. In their study, Joseph et al showed that lower allergy prevalence was associated with higher transforming growth factor beta (TGF-β) levels in breast milk [21].…”
Section: Immune Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Поскольку перегрузка железом способствует развитию СOVID-19, были предприняты по иски хелаторов, которые привели исследователей к обнаружению эффективного природного железосвязывающего гликопротеина -лактоферрина [40].…”
unclassified